Tunable function of feeding network and SPDT switch for WIMAX application - N. Edward; N. A. Shairi; Z. Zakaria; Tole Sutikno; I. D. Saiful Bahri (Institute of Advanced Engineering and Science, 2019)
A tunable circuit that functions as a power divider and a single pole double throw (SPDT) switch is proposed in this paper. The power divider design was based on the conventional Wilkinson power divider (WPD). Since WPD design has wideband properties, a modification was made in the design to make it narrowband so that it will only work for WiMAX applications. Two shorted stubs were introduced in the transmission line of the output ports to encounter the mismatch when the function was switched to an SPDT switch. Rogers RO4350 (er = 3.48, h = 0.508mm) was used as a substrate material and copper (thickness = 0.035 mm) related to patch of this proposed design. When the circuit functioned as a power divider, the simulated result showed S11 < -16 dB, S12 > 3.97 dB, and S23 < -14 dB for both operating frequencies of 2.5 GHz and 3.5 GHz. On the other hand, when the circuit functioned as an SPDT switch and port 2 was in the ON state, the simulated result showed S11 < -35 dB, S12 > -1.1, S13 < -16 dB, and S23 < 18 dB for both operating frequencies of 2.5 and 3.5 GHz. The proposed design showed a good performance as a power divider and an SPDT switch, thus, it can be used for multifunctional microwave circuits.